PENGARUH KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN SKUB PADA PT GAM-KMS DESA TEBEDAK KABUPATEN LANDAK - Egie, Lidia; Witarsa, Witarsa; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The purpose of this research is to find: 1) Compensation for SKUB employees, 2) Job satisfaction of SKUB employees, 3) The effect of compensation on SKUB employee job satisfaction. The form of this research is a correlation/associative study with a quantitative approach. The population is SKUB (General Monthly Employee Status) employees who work at PT Gapura Alas Makmur-Kebun Makmur Sentosa (PT GAM-KMS) in Tebedak Village, Landak Regency. A sample of 118 employees was obtained using a proportional random sampling technique. The data collection method uses questionnaires or questionnaires which are distributed directly to respondents and uses documentation methods to complete the data needed to conduct research. The analysis was carried out using simple linear regression analysis techniques. The results of this research show that: 1) The effect of providing compensation to SKUB employees is very high with a percentage of 87.97%. 2) SKUB employee job satisfaction in the company is classified as high with a percentage of 88.26%. 3) Compensation has an influence on SKUB job satisfaction at PT Gapura Alas Makmur-Kebun Makmur Sentosa (PT GAM-KMS) in Tebedak Village, Landak Regency by 39.2%. Based on the SPSS results, a sig value = 0.000 0.05 was obtained, so it was rejected and accepted. This means that "There is a significant influence between compensation on job satisfaction of SKUB employees at PT Gapura Alas Makmur-Kebun Makmur Sentosa (PT GAM-KMS) in Tebedak Village, Landak Regency."